2000
DOI: 10.1002/1521-186x(200010)21:7<491::aid-bem2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low frequency, low amplitude magnetic fields on the permeability of cationic liposomes entrapping carbonic anhydrase: I. Evidence for charged lipid involvement

Abstract: The influence of low frequency (4-16 Hz), low amplitude (25-75 mu T) magnetic fields on the diffusion processes in enzyme-loaded unilamellar liposomes as bioreactors was studied. Cationic liposomes containing dipalmitoylphosphatidylcholine, cholesterol, and charged lipid stearylamine (SA) at different molar ratios (6:3:1 or 5:3:2) were used. Previous kinetic experiments showed a very low self-diffusion rate of the substrate p-nitrophenyl acetate (p-NPA) across intact liposome bilayer. After 60 min of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Thus, to verify if a dipolar structure of the SA is a plausible target for the interaction of the ELF-EMF with lipid membrane [Ramundo-Orlando et al, 2000], we propose here a simple model for analyzing the behavior of a dipole inserted in a complex environment.…”
Section: Theoretical Studies and Basic Calculationssupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, to verify if a dipolar structure of the SA is a plausible target for the interaction of the ELF-EMF with lipid membrane [Ramundo-Orlando et al, 2000], we propose here a simple model for analyzing the behavior of a dipole inserted in a complex environment.…”
Section: Theoretical Studies and Basic Calculationssupporting
confidence: 83%
“…These experimental conditions were used in previous work with CA-loaded liposomes [Ramundo-Orlando et al, 2000]. The results in Table 1 show that the esterase activity of CA was not impaired by ELF magnetic ®elds exposure in this range of frequencies.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…However, Essence of performing such this study refers to researches done by Desai et al [11] and Mathie et al [12] and Ramundo et al [13] which investigated effects of the radiations on intra membrane structures like proteins and ion channels. This study showed dis-compaction and non uniformity of intranuclear chromatin and its incongruity and heterogenic feature ( Figure 1H) that according to De Iuliis [14] and Aitken's [15] results can change the ultra structure of living tissues.…”
Section: Discussionmentioning
confidence: 99%